Detection of Fastidious Vaginal Bacteria in Women with HIV Infection and Bacterial Vaginosis - Caroline Mitchell; Carla Moreira; David Fredricks; Kathleen Paul; Angela M. Caliendo; Jaclynn Kurpewski; Jessica Ingersoll; Susan Cu-Uvin (Hindawi Limited, 2009)
Background. Fastidious bacteria have been associated with bacterial vaginosis (BV) using PCR methods. We assessed the prevalence of these bacteria in HIV-1 infected women and their relationship with vaginal pH and shedding of HIV-1 RNA. Methods. 64 cervicovaginal lavage (CVL) samples were collected from 51 women. Vaginal microbiota were characterized using 8 bacterium-specific quantitative PCR assays. Results. Women with the fastidious bacteria Bacterial Vaginosis Associated Bacterium (BVAB) 1, 2, and 3 showed a trend to increased HIV-1 shedding (OR 2.59-3.07, P=.14-.17). Absence of Lactobacillus crispatus (P<.005) and presence of BVAB2 (P<.001) were associated with elevated vaginal pH. BVAB1, 2, and 3 were highly specific indicators of BV in HIV-infected women, with specificities of 89%-93%. Conclusions. Fastidious bacteria (BVAB 1, 2, and 3) remain specific indicators of BV in HIV-infected women, and BVAB2 may contribute to the elevated vaginal pH that is a hallmark of this syndrome.